Is the Transfer of Russian Engineering Education to the American Liberal Arts System Relevant? - A. I. Rudskoy; A. I. Borovkov; P. I. Romanov (Moscow Polytechnic University, 2021)
In his Address to the Federal Assembly on January 15, 2020, the President of Russia set the task "to enable students after their second year to choose a new direction or program of study, including related professions". Solving this problem requires transformation of the higher education system in Russia. Discussion has arisen in the educational community about the ways of this transformation. One of the possible options was the transfer of Russian education to the American Liberal Arts system. In order to verify the feasibility of using the Liberal Arts system for the training of engineers, a comparative study was carried out. As a result, it was concluded that proposals to replace the Russian system of higher education with the American Liberal Arts system for engineering education are not relevant, because the main basic goals and principles of building these systems coincide and the existing differences are due to the specifics of engineering activities.